Fabrication and Electrochemical Performance of Al-Doped ZnO Nanosheets on Graphene-Based Flexible Substrates - Yu, Qi; Rong, Ping; Ren, Shuai; Jiang, Liyun; Li, Yapeng (Frontiers in Materials, 2019)
In this work, Al-doped ZnO (AZO) nanosheets (NSs) were successfully synthesized on graphene-coated polyethylene terephthalate (GPET) flexible substrate via hydrothermal method. Studies have indicated that with the addition of Al3+, the nanostructure of ZnO gradually grows from nanorods (NRs) to NSs, and the (100), (002), and (101) diffraction peak strength of ZnO that grows perpendicularly to the substrate along the c-axis weakened. The mechanism of hydrothermal growth of AZO/GPET was also studied. The electrochemical properties of the samples were investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), and it was concluded that AZO NSs grown on GPET substrates has better capacitance performance than undoped ZnO NRs.